2020
DOI: 10.1021/acsami.0c16647
|View full text |Cite
|
Sign up to set email alerts
|

Ti-Modified LaFeO3/β-SiC Alveolar Foams as Immobilized Dual Catalysts with Combined Photo-Fenton and Photocatalytic Activity

Abstract: Ti-modified LaFeO3/β-SiC alveolar foams were used as immobilized, highly robust dual catalyst with combined photo-Catalytic Wet Peroxide Oxidation (CWPO) and photocatalytic activity under UV-A light. They were prepared by incipient wetness impregnation of a β-SiC foam support, by implementing a sol-gel Pechini synthesis at the foam surface in the presence of dried amorphous sol-gel titania as titanium source. Physico-chemical and catalytic features suggest the stabilization at the foam surface of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Taking the removal of 4-clorophenol from water as a model reaction, the authors demonstrated that their catalyst offers the advantages of both processes achieving full total organic carbon (TOC) conversion. Moreover, the β-SiC support allows the catalyst macroscopic shaping to overcome all technical issues related to powdery materials and ensures its easy recycling without activity loss …”
Section: Catalytic Applicationssupporting
confidence: 60%
See 1 more Smart Citation
“…Taking the removal of 4-clorophenol from water as a model reaction, the authors demonstrated that their catalyst offers the advantages of both processes achieving full total organic carbon (TOC) conversion. Moreover, the β-SiC support allows the catalyst macroscopic shaping to overcome all technical issues related to powdery materials and ensures its easy recycling without activity loss …”
Section: Catalytic Applicationssupporting
confidence: 60%
“…Moreover, the β-SiC support allows the catalyst macroscopic shaping to overcome all technical issues related to powdery materials and ensures its easy recycling without activity loss. 666 At odds to what was reported by Robert's group where SiC does not actively participate in the photocatalytic process, Juarez-Ramirez et al showed a synergistic effect between TiO 2 and SiC semiconductors through the interaction of their respective CV and VB bearing ideal potential values. The composite demonstrated the reduction of the recombination rate of charge carriers thus enhancing the degradation of methylene blue and indigo carmine chosen as model water polluting dyes.…”
Section: Photochemical Processesmentioning
confidence: 89%
“…Open-cell alveolar foams have attracted significant interest as supports for immobilizing photocatalysts because of their ability of acting as an active static mixer while working at an ultralow pressure drop and maintaining a better light transmission than packed-bed supports [12,13]. Self-bonded β-SiC foams stand out compared to polymer, metallic, and other ceramic foams [14,15] in terms of thermal/chemical stability, allowing them to withstand harsh conditions for catalyst immobilization or for the reaction of application, and of density of oxygenated surface groups for catalyst anchorage, since their surface consists of an amorphous SiO 2 overlayer, formed upon thermal treatment and characterized by a high density of hydrophilic hydroxyl groups [16].…”
Section: Introductionmentioning
confidence: 99%
“…Surface-bound nanomaterials are key components in many clean energy techniques from lithium batteries, solar absorber, 1 solar-driven interfacial evaporation in desalination, [2][3][4] photocatalytic reactions, [5][6][7] to wastewater treatment and environment remediation by photolysis. 7,8 Maximizing the performance and functionalities of the materials requires control of spatial distribution and coverage of nanomaterials deposited on a supporting substrate.…”
Section: Introductionmentioning
confidence: 99%